Concept of Islam Kaffah in Islamic Education Curriculum - Ayu, Sovia Mas (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Religious works in themselves serve as a guide or hudan li al-nas (instructions for human life). The presentation of the teachings of the Prophet includes two forms: First, the form of study groups (teaching), and second, uswah hasanah (good example). Ta'lim (teaching) is considered necessary, in order to anticipate the progress and development of life sciences community and responsibility. The position of science in Islam is very strong, demanding to be mastered by all people, even if within certain limits according to his ability. The perception of al-Islam cannot be separated from an understanding of the sources of his teachings, namely the Quran and al-Sunnah and the environment (people and nature). It is also important to integrate learning process for both sources in various corners. This paper will examine the concept of al-Islam Kaffah mentioned in the Quran in Islamic education curriculum in formal educational institutions. Descriptive qualitative study is used to illustrate the concept of Islamic education that can implement Islamic values towards al-Islam kaffah mentioned in the Quran.